Exploring Intestinal Protozoa as a Causative of Diarrhea in Children of Thi- Qar Province - Athouf, Dhuha A. (American Journal of Biology and Natural Sciences, 2025)
Background: This study is cross-sectional. Common causes of diarrhea in children are intestinal parasites, which have notable worldwide prevalence especially in underdeveloped countries. Common infectious diseases caused by intestinal parasites cause many health problems and compromise growth and physical development. In children, severe infectious diarrhea mostly results from poor environmental sanitation and hygiene, lack of water, and poverty. Objectives: The purpose of this study was to Investigate the intestinal protozoa causes diarrhea that infects children and know the factors that affect intestinal parasite (protozoa) infection. Methodology: Fifty fecal samples were collected from pediatric patients experiencing diarrhea. All samples included both genders (25 males and 25 females) and age groups from 1 day to 5 years, collected at Bint Al-Huda Teaching Hospital, Al-Haboubi Teaching Hospital, and Mohammed Al-Moussawi Children’s Hospital from various locations in Thi-Qar province between October 1, 2024, and January 10, 2025. Results: The investigation of intestinal protozoa was conducted through stool examination utilizing both unstained and stained preparations of stool smears. Two species of intestinal parasites were identified. Entamoeba histolytica (69.44%) and Giardia lamblia (30.56%) are among them. Among 50 youngsters, 36 (72%) were identified as infected with intestinal protozoan parasites, with a greater incidence in males at 19 (52.78%) compared to females at 17 (47.22%). A statistically significant difference in the prevalence of intestinal parasites was observed based on sex (P < 0.05). Distribution of infection with intestinal parasites was greater in the age range (1-5) year (44.44 %) and lowest (13.89%) in the children less than 1month of age. The change was statistically significant (P < 0.05). The prevalence of intestinal parasite infections was highest in the months of October to November (63.89%) and lowest in December to January (36.11%). A statistically significant difference in infection rates was observed between these months (P < 0.05). Conclusions: Entamoeba histolytica exhibits greater prevalence in Thi-Qar province. Age, gender, and month of infection are factors that affect intestinal parasitic infection.